Characterization of a deletion in the Hsp70 cluster in the bovine reference genome. (31st May 2017) - Suqueli García, M. F.; Castellote, M. A.; Feingold, S. E.; Corva, P. M.
Summary: The 70 kilodalton heat shock proteins (Hsp70) are highly conserved molecular chaperones which have a crucial role in the stress response of the cell. In mammals, the Hsp70 proteins are encoded by a cluster of three genes: HSPA1A, HSPA1B and HSPA1L . In bovines, this cluster is located on chromosome 23 downstream of the major histocompatibility complex (BoLA). We detected inconsistencies in the location of markers on the Hsp70 genes reported in the literature that pointed to a potential deletion in the bovine reference genome UMD 3.1.1. An in silico analysis of the bovine genomic region of the Hsp70 cluster, using available information from public databases, confirmed the existence of a deletion of 11.1‐kb spanning the HSPA1B gene and the intergenic region between HSPA1B and HSPA1A . Although we originally considered this an assembly error, it is most likely a particular condition of L1 Dominette 01449, the cow sequenced in the Bovine Genome Project. Moreover, we suggest a new classification of bovine Hsp70 sequences reported in NCBI and a reassignment of the location of SNPs from dbSNP that map to the deletion on BTA23. We also compared the location of selected transcription factor binding sites on the promoters of HSPA1A and HSPA1B . The results generated in the present work could be helpful to refine the reference genome of an important livestock species and also to understand the role and the regulation of the bovine Hsp70 genes.